(3cJGH aj PcQ GdYTQI GdoeHTQjf HGdLfIs - (3eMehO Hf YeQ Hf eMeO Hf CMeO GdNhGQRej GdReNTQqj, LGQ Gddg, CHh GdbGSe,(B538 (3g`s
(3ChdgG (B:s
(3hHYO , aEfg hQO aj UMjM GdBKGQ GdeSfOI Yf GdYdeGA GdcHGQ Cf QShd Gddg Udi Gddg Ydjg hSde bGd(B: (3YfO PcQ GdUGdMjf JfRd GdQMeI hGdQMeI dG efOhMI dCMO YfgG s
(3BNQgG (B:s
(3PcQ ChdGOg QVj Gddg Yfg PcQ GHf SYjO QMeg Gddg Cfg cGf dg ef GdhdO LQjQ hYejQ QVj Gddg Yfge CLeYjf hMTQfG eYge aj ReQI SjO GdeQSdjf s
(3Vef eLehY s
(3fSNI NRGFfjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B178 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B186 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B402s
(3HQhcdeGf (B- (3GdLRA (B1 - (3U (B292 ; (3HQhcdeGf edMb (B- (3GdLRA (B1 - (3U (B511 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B339 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK , CQVg s
Keywords: (3GdJGQjNs